+0

# Help. ​

0
41
1
+987

Help.

NotSoSmart  Oct 23, 2017
Sort:

#1
+78604
+1

3x + 2y +  z  = 7     (1)

5x + 5y + 4z  = 3    (2)

3x + 2y + 3z  = 1    (3)

The object, NSS, is to eliminate a variable and end up with 2 equations with two unknowns

We can choose any variable that we want......here....z seems easiest

Multiply the first equation by -4  and add it to equation 2

-12x - 8y -  4z = -28

5x  + 5y + 4z =   3

________________

-7x - 3y          =  -25         →  7x + 3y = 25      (4)

Multiply the first equation by -3 and add it to to the 3rd equation

-9x - 6y - 3z = -21

3x  + 2y + 3z = 1

_________________

- 6x - 4y      =  -20     →  6x + 4y  =  20    (5)

Multiply (4) by  4   and (5) by  -3

28x +12 y = 100

-18x -  12y  =  -60         add these together

10x =  40      divide both sides by 10

x = 4

Using (5) to find y, we have

6(4) + 4y = 20

24 + 4y  = 20    subtract24 from both sides

4y  = -4      divide both sides by 4

y = - 1

And using   3x  + 2y + 3z = 1  to find z, we have

3 (4) + 2 (-1) + 3z  = 1

12 - 2 + 3z  = 1

10 + 3z  = 1    subtract 10 from both sides

3z = -9       divide both sides by

z = -3

So....{ x , y, z }  =  { 4, -1, -3 }

CPhill  Oct 23, 2017

### 18 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details